Movements and Activity Budgets of Caribou Near Oil Drilling Sites in the Sagavanirktok River Floodplain, Alaska - Fancy, Steve G. (ARCTIC, 1983)
Movements and activity patterns were compared for caribou (Rangifer tarandus granti) near two active drilling sites on the periphery of the Prudhoe Bay oilfield and for caribou from a control site. Caribou on the experimental and control sites had similar movement rates and activity budgets, but many localized responses to the roads, pipelines, vehicle traffic, and other structures and activities were observed. Insect harassment had an appreciable effect on caribou movements and activity budgets. Groups harassed by insects moved approximately twice as fast and spent at least 50% less time lying and feeding than did unharassed groups. Of the 99 groups that approached a road, pipeline, and/or drill site, 70.7% crossed directly, 19.2% detoured around the drill site, and 10.1% reversed direction and left the study area. No evidence was found that caribou cows and calves were avoiding the area because of drilling operations.Key words: caribou, Rangifer tarandus granti, movements, disturbance, insect harassment, Prudhoe Bay, petroleum development Les mouvements et activités du caribou (Rangifer tarandus granti) sont comparés prés de deux sites de forage actif dans la périphérie du champ de pétrole de la baie Prudhoe ainsi que dans un site de contrôle. Les caribous dans les sites expérimentaux et de contrôle présentaient un taux de mouvement et un régime d'activité semblables, mais on observa un bon nombre de réactions localisées aux routes, aux pipelines, à la circulation de véhicules et à d'autres structures et activités. Les tourments infligés par les insectes ont eu un effet appréciable sur les mouvements et le régime d'activité. Les groupes tourmentés par les insectes se déplaçaient environ deux fois plus vite que les groupes non tourmentés, et passaient environ 50% moins de temps à se nourrir et à se reposer que ces derniers. Des 99 groupes ayant approché une route, un pipeline et/ou un site de forage 70.7% traversaient directement, 19.2% faisaient un détour autour du site de forage, et 10.1% faisaient ...